2013 IEEE 9th International Conference on Wireless and Mobile Computing, Networking and Communications (WiMob) 2013
DOI: 10.1109/wimob.2013.6673355
|View full text |Cite
|
Sign up to set email alerts
|

How effective is to look at a vehicular network under a social perception?

Abstract: Abstract-Vehicular Mobility is strongly influenced by the speed limits and direction of the public roads. At the same time, the driver's behavior produces great influences in vehicular mobility. People tend to go to the same places, at the same day period, through the same trajectories, which le ad them to the appearance of driver's daily routines. These routines lead us to the study of mobility in VANETs under a social perspective and to investigate how effective is to explore social interactions in this kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Let us assume a generic network expressed in terms of graph G (V, N ), where V and N are the sets of nodes, and edges, respectively. Based on the works in [51], [56], [57], [58], [59], and through graph theoretic and functionality models, we can distinguish the following centrality metrics: 1) Degree Centrality of a node v i.e., d (v), is the simplest centrality metric that refers to the number of direct connections the node v has to its neighbors. It can be expressed as:…”
Section: A Content Dissemination In Vsnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us assume a generic network expressed in terms of graph G (V, N ), where V and N are the sets of nodes, and edges, respectively. Based on the works in [51], [56], [57], [58], [59], and through graph theoretic and functionality models, we can distinguish the following centrality metrics: 1) Degree Centrality of a node v i.e., d (v), is the simplest centrality metric that refers to the number of direct connections the node v has to its neighbors. It can be expressed as:…”
Section: A Content Dissemination In Vsnsmentioning
confidence: 99%
“…In [58] Cunha et al present the characterization and evaluation of a realistic vehicular trace in order to study the vehicles' mobility in the context of social behaviors. Through numerical analysis, the authors identify peculiar social characteristics in vehicular networks, and how the use of these metrics can improve the network performance of communication protocols and services.…”
Section: B Social Features In Vsnsmentioning
confidence: 99%
“…In our initial work [2], we showed an social analysis of a trace mobility. In this work, we had classified the metrics according to mobility features.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Cunha et al [58] showed that vehicles tend to show a similar behaviour and routines in terms of mobility. The mobility of vehicles can be mapped as a social network, following the same basic laws of degree distribution and distance among nodes.…”
Section: Social Network Analysis In Siovsmentioning
confidence: 99%